Natural convection and entropy production in hybrid nanofluid filled-annular elliptical cavity with internal heat generation or absorption - Tayebi, Tahar; Öztop, Hakan Fehmi; Chamkha, Ali J. (Elsevier, 2020)
This study is an attempt to understand the characteristics of heat transfer by natural convection, flow, and entropy generation of Cu-Al2O3/H2O based hybrid nanoliquid filled-annulus delimited by two elliptic cylinders considering internal heat generation or absorption (IHG/A) phenomenon. The buoyancy-driven flow is induced by a thermal gradient between isothermal and differentially heated inner and outer cylinders. A numerical solution of the governing equations in the dimensionless and non-primitive form is performed using the technique of finite volume discretization. Impacts of diverse parameters of the study such as copper-alumina nanoparticles volumic concentration, Rayleigh number, and dimensionless internal heat generation or absorption parameter on the thermohydrodynamic characteristic and entropy generation are examined. An analysis of the results showed that the combined effects of internal heat generation/absorption and hybrid nanoliquid significantly alter the hydrothermal characteristics, heat transfer rate, and entropy generation within the annulus.
Keywords: Natural convection; Entropy generation; Heat generation or absorption; Hybrid nanofluid; Elliptical annulus